Prognostic role of PIK3CA and TP53 in human papillomavirus–negative oropharyngeal cancers. Issue 3 (June 2018) - Resteghini, Carlo; Perrone, Federica; Miceli, Rosalba; Bergamini, Cristiana; Alfieri, Salvatore; Orlandi, Ester; Guzzo, Marco; Granata, Roberta; Galbiati, Donata; Cavalieri, Stefano; Locati, Laura; Licitra, Lisa; et al.
Background: Human papilloma virus (HPV)–negative oropharyngeal squamous cell carcinomas (OPCs) have a poorer prognosis and best management is an unmet need. We studied the prognostic role of epidermal growth factor receptor (EGFR) and PIK3CA amplifications and TP53 functional status. Methods: Between 1992 and 2000, 90 consecutive patients with OPCs were treated with surgery, followed by radiotherapy in case of high-risk pathologic features. Of those, 73 cases were HPV-negative and therefore were selected for molecular analysis ( PIK3CA and EGFR fluorescent in situ hybridization [FISH] analysis and TP53 mutation analysis). Results: FISH analyses of EGFR and PIK3CA were successfully conducted on 69 and 63 of 73 tumor samples, respectively. EGFR alterations were detected in 43% of patients but just 7% showed amplification. Seven cases (11%) carried PIK3CA amplification and 18 (29%) gene gain or high polysomy. TP53 was detected as nonfunctional in 24 of 67 (36%) successfully analyzed cases. Both univariable and multivariable analysis showed statistically significantly worse disease-free survival (DFS) for patients with PIK3CA disomy compared to those with gene gain or high polysomy. No differences in overall survival or DFS for EGFR and TP53 alteration were evident. The combined evaluation of PIK3CA and TP53 showed that PIK3CA gene copy number gain separated a population with better outcome, defining an overall worse prognosis population (disomy) now clearly further divided according to TP53 functional status. Conclusion: PIK3CA gene copy number increase is associated with a favorable clinical outcome in HPV-negative OPCs treated with surgery ± postoperative radiotherapy. In patients without PIK3CA alteration, TP53 nonfunctional mutations are associated with poor prognosis.